Les passeuses de parole. Une position féminine dans le théâtre burlesque de l’alliance (Andes) - Camille Riverti (Les Cahiers ALHIM)
Focusing on the burlesque performances of the alliance in the Andes, the article examines the singular ways in which local women engage in the playful field as word-mongers. Listening attentively to what these voices say in Quechua, this article questions this feminine peri-theatre. Based on a fine analysis of burlesque scenarios and interactional strategies, it dissects the ways in which women play to cancel, dampen and subvert the ordinary differential valence of the sexes. Showing that interactional power can emanate from the periphery, the article depicts, in short, a political theatre where gender relations are questioned and worked on through humour.